Apologi Biblikal atas Tuduhan Yesus, Manusia yang di-Tuhankan - Baskoro, Paulus Kunto (Sekolah Tinggi Teologi Hagiasmos Mission, 2021)
Jesus is a phenomenal person and character in the journey of the story of human life. For believers, Jesus is a glorious person and has tremendous authority as Lord and Savior. Believers must have firm belief in the person of Jesus. However, in the course of theological understanding, the person of Jesus underwent extraordinary debates, eventually emerging ideas that were very contrary to the truth of the Bible or the Word of God. One of the misconceptions about Jesus, is that Jesus is a man who is deified. This is an understanding that is still a bitter issue today among non-believers, as well as in some Christian groups. Through the descriptive qualitative method with the literature study approach, the author describes the purpose of biblical aplogetics for the debate about the person of Jesus, so it must be taken seriously again from the basic truth of the Bible which is the foundation of believers as well as evidence of historical facts that cannot be denied. This study seeks to describe and discuss the correct principles about Jesus as God and not Jesus as a human being who was deified based on the Bible or the Word of God. So that the greatest hope of this research, everyone realizes and believes that Jesus is also a true God. In terms of the truth of God's Word. Abstrak Yesus adalah pribadi serta tokoh yang sangat fenomenal dalam perjalanan kisah kehidupan manusia. Bagi orang percaya, Yesus adalah pribadi yang mulia dan memiliki otoritas yang dahsyat sebagai Tuhan dan Juruselamat. Orang percaya harus memiliki keyakinan teguh akan pribadi Yesus. Namun dalam perjalanan pemahaman teologis, pribadi Yesus mengalami perdebatan yang luar biasa dengan akhirnya muncul paham-paham yang sangat bertolak belakang dengan kebenaran Alkitab atau Firman Tuhan. Salah satu pemahaman yang salah tentang Yesus, adalah Yesus adalah manusia yang di-Tuhankan. Ini menjadi pemahaman yang sampai hari ini masih menjadi persoalan sengit dikalangan orang-orang yang belum percaya Yesus, maupun dalam beberapa kelompok Kristen. Melalui metode kulaitatif dseskriptif dengan pendekatan studi pustaka penulis mendeskripsikan tujuan aplogetika biblika bagi perdebatan tentang pribadi Yesus, maka harus kembali diperhatikan secara serius dari dasar kebenaran Alkitab yang menjadi pondasi orang percaya serta bukti fakta sejarah yang pasti tidak bisa dipungkiri kebenarannya. Penelitian ini berusaha memaparkan dan membahas prinsip-prinsip yang benar tentang Yesus adalah Tuhan dan bukan Yesus adalah manusia yang di-Tuhankan dengan berdasarkan Alkitab atau Firman Allah. Sehingga harapan terbesar dari penelitian ini, setiap orang menyadari dan percaya bahwa Yesus juga adalah Allah yang sejati. Dengan ditinjau dari kebenaran Firman Tuhan.